AEROBIC ENDURANCE (VO2MAX) LEVEL OF PHYSICAL EDUCATION COED IN SRIWIJAYA UNIVERSITY - IYAKRUS, IYAKRUS (Sriwijaya University Learning and Education International Conference, 2016)
This research aims to know aerobic endurance (vo2max) level of physical education coed in sriwijaya university. This research is descriptive quantitative research. The method is engineering test and data measurement aerobic endurance test with bleep to know the level of coed vo2max. The sample is 42 physical education coed of Sriwijaya University. The result shows 14 coed (33%) are exellent, 19 coed (45%) are good, 4 coed (9.6%) are fair, and 5 coed (12%) are poor. Based on presentase, the coed of physical education in Sriwijaya University have a good aerobic endurance (Vo2max) level, only 4 coed have poor aerobic endurance (Vo2max) level. Sugessted to physical education program study to increase coed aerobic endurance level thought coaching sport branch at least 2 times a week.